Ahed Tamimi's Position in Some Arab News: Critical Discourse Analysis of Sara Mills - Wulandari, Betty Ayunda; Surur, Misbahus (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2024)
The sexual harassment case against young Palestinian activist Ahmed Tamimi took place in 2018. The research aims to analyze how media language is used to convey information to readers through an emphasis on the actors described in the Arabic news on the harassment of a woman named Ahed Tamimi using Sara Mills' critical discourse analysis theory. This research is descriptive qualitative research, which is a type of library research. The primary data source for this research is the news at the Al Jazeera, Sputnik Arab, and Al Watan voices. This research is also supported by secondary data in the form of books, journal articles, and similar news that support the research. Critical discourse analysis of Sara Mills is used as an analysis technique for the data. Research findings show that Ahed Tamimi is positioned as an object in the news, not as the main subject in news sources. It is because the news of the sexual harassment of Ahed Tamimi was conveyed through information from other actors, namely her lawyer. This lawyer becomes the subject of the storyteller, who explains and describes the news. Thus, this news is not presented directly by the female victim, namely Ahed Tamimi. In addition, this news text provides an overview of the subject and object of the storytelling, thus influencing the way the text is presented to the reader. In addition, this news text reflects gender elements because the event is conveyed and described from the male side or perspective, either from a lawyer or Israeli military spokesperson, not from the perspective of women or Ahed Tamimi as a victim of sexual harassment Abstrak Kasus pelecehan seksual terhadap aktivis muda Palestina Ahmed Tamimi terjadi pada tahun 2018. Penelitian ini bertujuan untuk menganalisis bagaimana bahasa media digunakan untuk menyampaikan informasi kepada pembaca melalui penekanan pada aktor yang digambarkan dalam berita berbahasa Arab tentang pelecehan terhadap seorang wanita bernama Ahed Tamimi menggunakan Teori analisis wacana kritis Sara Mills. Penelitian ini merupakan penelitian kualitatif deskriptif dengan jenis penelitian kepustakaan. Sumber data primer penelitian ini adalah berita di Al Jazeera, Sputnik Arab, and Al Watan Voice. Penelitian ini juga didukung oleh data sekunder berupa buku, artikel jurnal, dan berita sejenis yang mendukung penelitian. Analisis isi digunakan sebagai teknik analisis data. Temuan penelitian menunjukkan bahwa Ahed Tamimi diposisikan sebagai objek dalam pemberitaan dan bukan sebagai subjek utama dalam sumber berita. Pasalnya, pemberitaan pelecehan seksual terhadap Ahed Tamimi disampaikan melalui informasi dari aktor lain, yakni pengacaranya. Pengacara inilah yang menjadi subjek narator yang menjelaskan dan menggambarkan berita tersebut. Jadi, kabar tersebut tidak disampaikan langsung oleh korban perempuan, yakni Ahed Tamimi. Selain itu, teks berita ini memberikan gambaran mengenai subjek dan objek cerita, sehingga mempengaruhi cara teks tersebut disajikan kepada pembaca. Selain itu, teks berita ini mencerminkan unsur gender karena peristiwa tersebut disampaikan dan digambarkan dari sisi atau sudut pandang laki-laki, baik dari pengacara atau juru bicara militer Israel, bukan disampaikan dari sudut pandang perempuan atau Ahed Tamimi sebagai korban pelecehan seksual